Photothermally Controlled Drug Release of Poly(d,l-lactide) Nanofibers Loaded with Indocyanine Green and Curcumin for Efficient Antimicrobial Photodynamic Therapy - Bernd Gutberlet; Eduard Preis; Valeri Roschenko; Udo Bakowsky (MDPI AG, 2023)
Chronic wound infections with antibiotic-resistant bacteria have become a significant problem for modern healthcare systems since they are often associated with high costs and require profound topical wound management. Successful wound healing is achieved by reducing the bacterial load of the wound and providing an environment that enhances cell growth. In this context, nanofibers show remarkable success because their structure offers a promising drug delivery platform that can mimic the native extracellular matrix and accelerate cell proliferation. In our study, single-needle electrospinning, a versatile and cost-efficient technique, was used to shape polymers into an applicable and homogeneous fleece capable of a photothermally triggered drug release. It was combined with antimicrobial photodynamic therapy, a promising procedure against resistant bacteria. Therefore, poly(d,l-lactide) nanofibers loaded with curcumin and indocyanine green (ICG) were produced for local antimicrobial treatment. The mesh had a homogeneous structure, and the nanofibers showed a smooth surface. Recordings with a thermal camera showed that near-infrared light irradiation of ICG increased the temperature (>44 °C) in the surrounding medium. Release studies confirmed more than 29% enhanced curcumin release triggered by elevated temperature. The antimicrobial activity was tested against the gram-positive strain Staphylococcus saprophyticus subsp. bovis and the gram-negative strain Escherichia coli DH5 alpha. The nanofibers loaded with both photosensitizers and irradiated with both wavelengths reduced the bacterial viability (~4.4 log10, 99.996%) significantly more than the nanofibers loaded with only one photosensitizer (<1.7 log10, 97.828%) or irradiated with only one wavelength (<2.0 log10, 98.952%). In addition, our formulation efficiently eradicated persistent adhered bacteria by >4.3 log10 (99.995%), which was also confirmed visually. Finally, the produced nanofibers showed good biocompatibility, proven by the cellular viability of mouse fibroblasts (L929). The data demonstrate that we have developed a new economic nanofiber formulation, which offers a triggered drug release, excellent antimicrobial properties, and good biocompatibility.